NuSTAR measurement of the cosmic X-ray background in the 3–20 keV energy band. Issue 3 (4th February 2021) - Krivonos, Roman; Wik, Daniel; Grefenstette, Brian; Madsen, Kristin; Perez, Kerstin; Rossland, Steven; Sazonov, Sergey; Zoglauer, Andreas
ABSTRACT: We present measurements of the intensity of the cosmic X-ray background (CXB) with the Nuclear Spectroscopic Telescope Array ( NuSTAR ) telescope in the 3–20 keV energy range. Our method uses spatial modulation of the CXB signal on the NuSTAR detectors through the telescope's side aperture. Based on the NuSTAR observations of selected extragalactic fields with a total exposure of 7 Ms, we have estimated the CXB 3–20 keV flux to be 2.8 × 10 −11 erg s −1 cm −2 deg −2, which is \! 8 per cent higher than that measured with HEAO-1 and consistent with the INTEGRAL measurement. The inferred CXB spectral shape in the 3–20 keV energy band is consistent with the canonical model of Gruber et al. We demonstrate that the spatially modulated CXB signal measured by NuSTAR is not contaminated by systematic noise and is limited by photon statistics. The measured relative scatter of the CXB intensity between different sky directions is compatible with cosmic variance, which opens new possibilities for studying CXB anisotropy over the whole sky with NuSTAR .